Penerapan Model Pembelajaran Kooperatif Think Pair Share (TPS) Pada Materi Pengukuran Panjang Menggunakan Satuan Tidak Baku Pada Siswa Kelas 1 Di SDN Pasirbitung - Deby Sabina; Indri Fitriani Juardi; Yunita Nursyamsi Dwi Putri; Komariah Komariah (Journal on Education, 2023)
Mathematics has a very important function in everyday life, helping humans solve various kinds of problems to meet the needs of life. In studying mathematics, there are four components that a person has, namely collaboration, communication, creative, and critical thinking, or abbreviated as 4C's. Problems related to learning achievement are things that are often experienced by all students. This condition also applies to grade 1 students of SDN Pasirbitung in mathematics subjects. Then, the Think Pair Share model was chosen to help students understand mathematics more easily. The Think Pair Share model is cooperative learning that prioritizes the process of cooperation in thinking and interacting in solving a problem. This learning model has been proven to improve student achievement. This study used the Classroom Action Research method. Broadly speaking, there are four stages that must be passed to conduct research with class action research methods, namely: Planning, Implementation, Observation, Reflection.